1999
DOI: 10.1086/306992
|View full text |Cite
|
Sign up to set email alerts
|

Optical versus Mid‐infrared Spectroscopic Classification of Ultraluminous Infrared Galaxies

Abstract: The origin of huge infrared luminosities of ultraluminous infrared galaxies (ULIGs) is still in question. Recently, Genzel et al. made mid-infrared (MIR) spectroscopy of a large number of ULIGs and found that the major energy source in them is massive stars formed in the recent starburst activity; i.e., ∼ 70%-80% of the sample are predominantly powered by the starburst. However, it is known that previous optical spectroscopic observations showed that the majority of ULIGs are classified as Seyferts or LINERs (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 63 publications
5
48
2
Order By: Relevance
“…See x 3.2 for further discussion. [See the electronic edition of the Supplement for a color version of this figure. ] Some authors have suggested that the shock-like line ratios found in the nuclei of galaxies classified as LINERs are due to the presence of shocks in outflowing gas ( Veilleux et al 1995;Lutz et al 1999;Taniguchi et al 1999). We can test this hypothesis by comparing the velocities in LINERs and H ii galaxies.…”
Section: Outflow Velocitymentioning
confidence: 90%
“…See x 3.2 for further discussion. [See the electronic edition of the Supplement for a color version of this figure. ] Some authors have suggested that the shock-like line ratios found in the nuclei of galaxies classified as LINERs are due to the presence of shocks in outflowing gas ( Veilleux et al 1995;Lutz et al 1999;Taniguchi et al 1999). We can test this hypothesis by comparing the velocities in LINERs and H ii galaxies.…”
Section: Outflow Velocitymentioning
confidence: 90%
“…The ionizing source of LINERs is currently a hot topic of debate (see Filipenko 1989 for a review) and has been attributed to either collisional ionization by fast shocks (Taniguchi et al 1999 ;Lutz et al 1999 ;Dopita & Sutherland 1995 ;Veilleux et al 1995) or photoionization by hot stars (Terashima et al 2000). In many of these studies, LINERs have been classiÐed using either the Heckman (1980) Veilleux et al (1995) selection criterion includes many of the objects which follow the curve of a possible starburst-AGN mixing sequence.…”
Section: Iner Classiðcationmentioning
confidence: 99%
“…The LINERs classed using our extreme mixing line fall in the region of the diagnostic diagram corresponding to either photoionization by a hard radiation Ðeld with a very low ionization parameter (Veilleux & Osterbrock 1987) or emission by fast shocks in a gas-poor environment without an ionizing precursor. The fast shocks may be due to one or a combination of the following ; superwind activity (Taniguchi et al 1999 ;Kim, Veilleux, & Sanders 1998), cooling Ñows (Dopita et al 1997), or a shocked accretion disk around an AGN (Dopita et al 1997). …”
Section: Iner Classiðcationmentioning
confidence: 99%
“…The polycyclic aromatic hydrocarbon (PAH) method has been extended to a larger sample (Lutz et al 1998 ;Rigopoulou et al 1999), allowing us to probe for evolutionary e †ects expected in a scenario in which starburst activity gives way to a quasar-like AGN buried inside the ULIRG (Sanders et al 1988a). Comparison of optical and MIR spectroscopic diagnostics (Lutz, Veilleux, & Genzel 1999 ;Taniguchi et al 1999) demonstrated surprisingly good agreement if optical LINERs are interpreted as starbursts. This Ðnding also suggests that AGNs in ULIRGs usually make their presence known optically at least in certain directions, instead of being fully embedded by large obscuring columns of dust.…”
Section: Introductionmentioning
confidence: 99%